Clostridium butyricum: a promising approach to enhancing intestinal health in poultry - Tang, Xiaopeng; Zeng, Yan; Li, Meijun (Frontiers in Veterinary Science, 2025)
The intestinal tract is essential for the overall health and productivity of animals, including poultry. Clostridium butyricum (C. butyricum) is a probiotic bacterium that has been shown to be a promising candidate for improving intestinal function and subsequently optimizing poultry growth. The beneficial effects of C. butyricum on intestinal health can be attributed to several key mechanisms. First, it helps maintain the balance of the intestinal microbiota by inhibiting the growth of harmful bacteria and promoting the proliferation of beneficial bacteria. This microbial homeostasis is essential for efficient nutrient digestion and absorption. Second, C. butyricum enhances the integrity of the intestinal barrier. It enhances the integrity of epithelial tight junctions, reducing the permeability of the intestinal mucosa and preventing the invasion of pathogenic substances. Furthermore, C. butyricum participates in the regulation of immune responses within the intestinal environment. It stimulates the production of immunoglobulins and cytokines, enhancing the immune defense mechanisms of the host. Additionally, C. butyricum influences the metabolism of nutrients in the intestine. It promotes the synthesis of short-chain fatty acids (SCFAs), which provide an energy source for intestinal cells and contribute to maintaining a healthy intestinal environment. Intestinal health is the basis of animal growth, and C. butyricum ultimately enhances production performance in poultry by regulating intestinal health. Studies have demonstrated that the administration of C. butyricum leads to improved feed conversion efficiency, increased weight gain, and enhanced overall production performance in poultry. However, further research is still needed to fully elucidate the complex interactions and precise molecular mechanisms underlying its beneficial effects. Understanding these mechanisms in detail will not only provide important insights for improving poultry production efficiency but also contribute to the development of more effective and sustainable strategies in the poultry industry.